2 Konings 9-10: "n Beoordeling van die Jehuvertelling as historiese bron - Breytenbach, J. H. (Hervormde teologiese studies, 1992)
2 Kings 9-10: An assessment of the Jehu narrative as a source of history A document’s value as a source of history is determined neither by the details it provides, nor by a contemporary date of origin, but by its nature. It is argued that 2 Kings 9-10 is a deuteronomistically edited version of an original Jehu narrative. The propagandistic nature of the original narrative as a legitimizing legend for the Jehu dynasty puts it out of contention as a reliable source of history.